FK students take consolation prize in Huawei ICT Competition 2022-2023 - Mimi Rabita, Abdul Wahit (2023)
KUALA LUMPUR, 24 November 2022 - The Faculty of Computing (FK), Universiti Malaysia Pahang (UMP) team, comprising Chin Yung Chee, Nur Atiqah Kamal and Amir Muhammad Hafiz Othman successfully took home a consolation prize worth RM600 in the Huawei ICT Competition 2022-2023 competition held at the Parkroyal Collection Hotel Kuala Lumpur recently.